Dual donor-acceptor covalent organic frameworks for hydrogen peroxide photosynthesis - Qin, Chencheng; Wu, Xiaodong; Tang, Lin; Chen, Xiaohong; Li, Miao; Mou, Yi; Su, Bo; Wang, Sibo; Feng, Chengyang; Liu, Jiawei; Yuan, Xingzhong; Zhao, Yanli; et al. (Nature communications, 2023)
Constructing photocatalytically active and stable covalent organic frameworks containing both oxidative and reductive reaction centers remain a challenge. In this study, benzotrithiophene-based covalent organic frameworks with spatially separated redox centers are rationally designed for the photocatalytic production of hydrogen peroxide from water and oxygen without sacrificial agents. The triazine-containing framework demonstrates high selectivity for H 2 O 2 photogeneration, with a yield rate of 2111 μM h −1 (21.11 μmol h −1 and 1407 μmol g −1 h −1 ) and a solar-to-chemical conversion efficiency of 0.296%. Codirectional charge transfer and large energetic differences between linkages and linkers are verified in the double donor-acceptor structures of periodic frameworks. The active sites are mainly concentrated on the electron-acceptor fragments near the imine bond, which regulate the electron distribution of adjacent carbon atoms to optimally reduce the Gibbs free energy of O 2 * and OOH* intermediates during the formation of H 2 O 2 . In this study, benzotrithiophene-based covalent organic frameworks with spatially separated oxidative and reductive reaction centers are rationally designed for photocatalytic production of H 2 O 2 from water and oxygen without sacrificial agents.